Kajian Teori Tentang Gembalakanlah Domba Allah Menurut 1 Petrus 5:1-11 Dan Aplikasinya Bagi Hamba Tuhan - Yasrin Mesalayuk (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2023)
There are actions of God's servants that are not in accordance with the true meaning of service in shepherding the congregation, and the importance of the meaning of Shepherd God's sheep to be significant for the life and service of God's servants. This article aims to explore the meaning implied in the writings of the Apostle Peter about the importance of shepherding God's church, and can build the personality, morals and spirituality of the church. This research uses a qualitative approach, by analyzing various sources such as books, novels, and updates related to the topic. The results of the analysis see the importance of God's servants interpreting the call to serve God to have a positive impact on the revival of the church. A servant of God must be able to be a blessing and example in all aspects of life so that the congregation truly believes that there is a God. The contents in this article are presented to make readers especially servants of God aware to serve God wholeheartedly, not with other motivations but for glory for God's name. This research is expected to contribute thoughts for God's servants in enriching themselves to become true Shepherds for God's Sheep friends.